Legal Protection of Local Product of Tambora Coffee as A Product of Geographical Indications in West Nusa Tenggara Province - Saputri, Ika; Taufik Firmanto; Ilyas; Zuhrah; Erham; Ainun Wulandari (Law and Justice, 2025)
This article is a legal research that discusses the legal protection of local tambora coffee products as a product of geographical indications in the province of West Nusa Tenggara (NTB). Writing this article aims to analyze the form of legal protection for local Tambora coffee products as a product of geographical indications in the Province of NTB. Method the method used is normative legal research, with several approaches used, namely, the statutory approach, the concept approach, the historical approach, and the analytical approach. Novelty , from this research it was found that legal facts had not been optimal in legal protection efforts for local Tambora coffee products as a product of geographical indications by the local government in NTB. The discussion from this study found the fact that legal protection efforts for local tambora coffee products as a product of geographical indications by the local government in NTB were not optimal. The local government in NTB needs to guarantee legal protection for Tambora coffee as a geographical indication in order to maintain the uniqueness of local products as a regional identity so as to avoid claims by other regions for local Tambora coffee products to be able to compete nationally and internationally. In conclusion , legal protection for local Tambora coffee products as a geographical indication product in NTB Province is not optimal. The lack of attention and supervision by the regional government in protecting the local Tambora coffee product as a geographical indication is at least indicated by the absence of regional legal products in the form of Regional Regulations (Perda) and/or Perkada which guarantee legal protection for local Tambora coffee products as a geographical indication product. Likewise, the implementation of legal protection and supervision of local Tambora coffee products as a product of geographical indications in the province of NTB still tends to be weak. The local government in NTB neglected to guarantee supervision and legal protection for local Tambora coffee products as a geographical indication. Even though it does not rule out the possibility that Tambora coffee can be branded /marketed as a product that is not only worth selling in the region but can also compete in national and international markets.